1998
DOI: 10.1007/pl00008630
|View full text |Cite
|
Sign up to set email alerts
|

Polymorphism of insertion sites of Ty1-copia class retrotransposons and its use for linkage and diversity analysis in pea

Abstract: A sample of 15 cultivars and 56 Pisum accessions from the JIC germplasm core collection has been studied using a modi®cation of the SSAP (sequencespeci®c ampli®cation polymorphisms) technique; the speci®c primer was designed to correspond to the polypurine tract (PPT) of PDR1, a Ty1-copia group retrotransposon of pea. Most of these SSAP products were shown to be PDR1 derived. The PDR1 SSAP markers are more informative than previously studied AFLP or RFLP markers and are distributed throughout the genome. Their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
151
1
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 150 publications
(172 citation statements)
references
References 26 publications
12
151
1
5
Order By: Relevance
“…The number of polymorphic SSAP fragments was about one and a half times that at AFLP ( Table 2). This result is in agreement with previous studies, for example, SSAP revealed two to threefold higher polymorphism per primer combination than AFLPs in Hordeum vulgare , Pisum (ELLIS et al, 1998), Triticum aestivum (QUEEN et al, 2004), and Anacardium occidentale (SYED et al, 2005). Moreover, SSAP was found to be the most informative system for estimating genetic diversity in tomato and pepper, in a study comparing SSAP with AFLP and SSR, producing about fourto nine-fold more polymorphic fragments than AFLP, and achieving the highest number of polymorphic bands per assay (MAY TAM et al, 2005).…”
Section: Ssap Vs Aflp Within Population Polymorphismsupporting
confidence: 93%
See 3 more Smart Citations
“…The number of polymorphic SSAP fragments was about one and a half times that at AFLP ( Table 2). This result is in agreement with previous studies, for example, SSAP revealed two to threefold higher polymorphism per primer combination than AFLPs in Hordeum vulgare , Pisum (ELLIS et al, 1998), Triticum aestivum (QUEEN et al, 2004), and Anacardium occidentale (SYED et al, 2005). Moreover, SSAP was found to be the most informative system for estimating genetic diversity in tomato and pepper, in a study comparing SSAP with AFLP and SSR, producing about fourto nine-fold more polymorphic fragments than AFLP, and achieving the highest number of polymorphic bands per assay (MAY TAM et al, 2005).…”
Section: Ssap Vs Aflp Within Population Polymorphismsupporting
confidence: 93%
“…Moreover, SSAP was found to be the most informative system for estimating genetic diversity in tomato and pepper, in a study comparing SSAP with AFLP and SSR, producing about fourto nine-fold more polymorphic fragments than AFLP, and achieving the highest number of polymorphic bands per assay (MAY TAM et al, 2005). In fact, one advantage of SSAP over AFLP is that higher levels of polymorphism are achieved (ELLIS et al, 1998), and fewer experiments are needed to generate the desired numbers of markers. SSAP generates more polymorphic markers than AFLP, probably due to the higher retrotransposition mutation rate relative to base mutation.…”
Section: Ssap Vs Aflp Within Population Polymorphismmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, reports were published evaluating the utility of TEs as source to develop molecular markers showing that TEs are highly polymorphic in terms of insertion sites and their internal structure (Ellis et al, 1998). Furthermore, TE-derived markers efficiently distinguished rice cultivars (Fukuchi et al, 1993).…”
Section: Discussionmentioning
confidence: 99%